Reduced Total Subgingival Bacterial Load in Patients with Ischaemic Stroke: A Case–Control Study of the Subgingival Microbiome and Carotid Atherosclerosis - Anita Siewko; Szymon J. Jurga; Maksymilian Aleksander Brzezicki; Izabela Wojtasz; Anita Nowak; Filip Czop; Maja Jurga; Iwona Towpik; Lukasz Dzieciuchowicz; Jaroslaw Piskorski; Radoslaw Kazmierski (Journal of Clinical Medicine, 2026)
Background/Objectives: Periodontal infection has been associated with ischaemic stroke, usually as a matter of burden: more pathogens, more vascular risk. That framing derives from stroke-free populations and rests largely on surrogate endpoints, chiefly carotid intima-media thickness (IMT). Whether it holds once stroke has occurred is unclear. Methods: We concurrently recruited 50 patients with ischaemic stroke and 48 stroke-free controls in western Poland. The subgingival microbiome was quantified for nine periodontal taxa and the total bacterial count, analysed on the log10 scale, with carotid IMT and standard biochemistry recorded in parallel. Associations with stroke were assessed by univariable and multivariable logistic regression with backward elimination, validated by optimism-corrected bootstrap. Results: Stroke patients had fewer teeth, deeper pockets, poorer oral hygiene, higher carotid IMT, white cell count and C-reactive protein (all p < 0.001). Treponema denticola and Tannerella forsythia were higher in cases and Fusobacterium nucleatum lower. Total bacterial load was lower in cases (mean 9.3, SD 0.9 versus 10.2, SD 0.9 log10, p < 0.001) and remained independently and inversely associated with stroke after adjustment (adjusted odds ratio 0.09 per ten-fold increase; 95% CI 0.02–0.38). This was not explained by tooth loss: load was uncorrelated with tooth number (rho 0.12, p = 0.26) and the association persisted after normalisation per tooth. Discrimination was high (c-statistic 0.970; optimism-corrected 0.940). Conclusions: The subgingival microbiome shifted with stroke in a taxon-specific manner, yet total bacterial load was lower, not higher, in stroke patients. Because microbial and inflammatory markers were measured after the event, these associations most plausibly reflect peri-stroke change and case–control structure rather than a forward-causal signal, marking a boundary on the periodontal-burden paradigm.